2019
DOI: 10.1088/1757-899x/640/1/012080
|View full text |Cite
|
Sign up to set email alerts
|

Clay soil stabilization using cement kiln dust

Abstract: This research investigated the suitability of cement kiln dust (CKD) on the stabilization of clayey soil extracted along a failed road section of Sango, Ota. Since CKD does not need any further processing or treatment, it is cheap as it is a waste product from cement production and can be utilized in powdery form. The suitability of CKD as a stabilizer is dependent on its performance on problematic soil. For this study, it was mixed with clayey soil in varying proportions of 7.5, 10, 12.5 and 15%. For each com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Literature sources indicate that BPD can be reused in a number of different ways for various purposes. As reported in many papers, the most common applications of BPD are in soil consolidation and stabilization [ 10 , 16 ]. BPD addition can lead to an increase in the shear strength of a soil and/or control the shrink-swell properties of a soil, thus improving the load-bearing capacity of a sub-grade to support pavements and foundations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature sources indicate that BPD can be reused in a number of different ways for various purposes. As reported in many papers, the most common applications of BPD are in soil consolidation and stabilization [ 10 , 16 ]. BPD addition can lead to an increase in the shear strength of a soil and/or control the shrink-swell properties of a soil, thus improving the load-bearing capacity of a sub-grade to support pavements and foundations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, using lime and cement is soil stabilization is not preferred because of an environmental issues [55]. Several studies interested in estimating the quantities of cement and global demand indicated that by 2050 the demand will reach 5 billion tons annually, which will constitute a real environmental threat to the natural resources and needed for the burning of raw materials [56]. In addition, the production of such industrial materials generates large amounts of carbon dioxide emissions (CO2), during the various stages of the process of burning materials and manufactured [9].…”
Section: Environmental Benefits Of Using Ckdmentioning
confidence: 99%
“…The production of one ton of cement generates from 600 to 700 kg of CKD. Statistics show that the quantities of CKD are estimated at about 2.6 billion tons annually [56]. As for the amount of CKD generated in the United States annually, it is estimated at 14.2 million tons, a large portion of them, approximately 64%, is reused as a raw material for the clinker kiln.…”
Section: Environmental Benefits Of Using Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in this field may be classified into three main categories: use byproduct from cement production operations, direct use of cement alone or mixed with other materials, and recycling of cement as concrete waste. The use of cement byproduct, especially cement kiln dust to stabilize or improve clay soil was cover by many studies (Adeyanju & Okeke, 2019;Amadi & Osu, 2018;Miller & Azad, 2000;Naseem et al, 2019). The mixing of cement with fly ash become commonly used to reduce the amount of cement used or improve specific geotechnical properties of soil (Amu et al, 2008;Chenari et al, 2018;Khemissa & Mahamedi, 2014).…”
Section: Introduction and Past Studiesmentioning
confidence: 99%